A practical guide to the synthesis of dinitroindolinyl-caged neurotransmitters - Ellis-Davies, Graham C R (2011)
This protocol describes a method for efficient chemical synthesis of dinitroindolinyl derivatives of glutamate and gamma-aminobutyric acid. these caged neurotransmitters are currently the most chemically and photochemically efficient probes for two-photon photolysis in living brain slices. the protocol only requires basic organic synthesis equipment, and no silica gel column chromatography or NMR spectroscopy is needed at any stage. Hplc is used to purify the caged transmitters at the end of the syntheses. thus, the synthesis of dinitroindolinyl-caged neurotransmitters is within the scope of a modestly equipped chemistry laboratory.